Nu@ge: A container‐based cloud computing service federation - Balouek‐Thomert, Daniel; Caron, Eddy; Gallard, Pascal; Lefèvre, Laurent (Concurrency and computation, 2017)
Summary The adoption of cloud computing is still limited by several legal concerns that customers may have, such as data sovereignty. In cloud computing, data can be physically hosted in sensible locations, resulting in a lack of control for companies. In this context, we present the Nu@ge project, which aims at building a federation of container‐sized datacenters in the French territory. Nu@ge provides a software stack that enables companies to interconnect independent datacenters in a national mesh. A software architecture is presented and implemented as a federation of small datacenters deployed in France. The proposed architecture enables cooperation between local customized‐cloud managers and a federation‐wide middleware. It uses monitoring information from facilities and performance indicators from physical servers for managing the system, preventing incidents and considering energy efficiency. Additionally, a prototype of a container‐sized datacenter has been validated and patented.